Uberização: liberdade ou precarização? Reflexões sobre o futuro do trabalho - Lopes, Fernanda Villalba (2022)
In the current scenario, technological changes have caused relevant impacts in the world of work/employment. Uberization has presented itself as a phenomenon that represents the platformization of part of productive social relations, at the same time that it is instituted within the resignification of contemporary entrepreneurship. In view of the above, the main objective of this research was to analyze the work relationships resulting from uberization that have been widely disseminated through virtual platforms, especially those of Ifood food delivery. In order to reach the objectives, a qualitative research was carried out, with the application of Critical Discourse Analysis and Content Analysis techniques, applied both in primary data (interviews) and in secondary data (reference about uberization). The results showed the precariousness of these labor relations, as well as the current stage of discussion in the literature of this recent global movement. Digital platform workers expose their physical and mental integrity at risk, with strenuous working hours, demonstrating the perpetuation of the idea that they are self-employed. The whole context presented brought reflections on uberization, whether it offers freedom or precariousness of work, as it has had an accelerated growth as a new working relationship. The demonstrated reality is that digital platforms, such as Ifood, transfer responsibility directly to the worker, who becomes solely responsible for managing their work and the risk of the enterprise, with no balance between the parties. It was considered that this contemporary work relationship of false entrepreneurship, as they demonstrate to the worker autonomy and freedom to choose working hours and deliveries, and end up capturing capitalist reproduction, that is, a distorted view of what really characterizes this new relationship. This situation was confirmed by the interview carried out with the platform's delivery people who handle their condition without rights.